The Children of HIROSHIMA - Okuda, Sadako Teiko; Vergun, Pamela Bea Wilson; Joseph, Paul, 1948-; Vergun, Robert; Thomasson, Catherine, 1901-1989; Donohoe, Martin; Ham, Sok-Hon, (Novel Peace Prize nominee) (London : Monoray, an imprint of Octopus Publishing Group Ltd, 2025)
Sadako Teiko Okuda was living in Osaki-shimo, an island off the mainland of Japan, when the bomb hit Hiroshima on the 6th of August 1945. Even sixty kilometers from the city, it was clear something horrific had happened. There was a blinding flash and the window next to Sadako smashed, a shard of glass leaving a painful burn on her neck. Soon, news came that her niece and nephew who lived in Hiroshima were missing. There was only one thing she could do - leave the relative safety of the island and set off into the city to find them. In the seven long days that followed, Sadako roamed the ruins of the city, desperately hoping that she would catch sight of her family and in the meantime coming across dozens of other children who were alone, distraught and in pain. Carrying only water and a little medicine, she did her best to nurse the children and offer what care, compassion and tenderness she could in unimaginable circumstances. And in turn, they helped her to find hope in the very darkest of times
Bibliography: pages [227]-230
Keywords: Okuda, Sadako; World War, 1939-1945 -- Personal narratives; Bombing, Aerial -- Japan; Atomic bomb victims; Hiroshima-shi (Japan) -- History -- Bombardment, 1945